2018
DOI: 10.1159/000495650
|View full text |Cite
|
Sign up to set email alerts
|

Targeting P-Glycoprotein: Nelfinavir Reverses Adriamycin Resistance in K562/ADR Cells

Abstract: Background/Aims: The emergence of multidrug resistance (MDR) caused by P-glycoprotein (P-gp) overexpression is a serious obstacle to the treatment of chronic myelocytic leukemia. In recent years, some clinical trials have shown that nelfinavir (NFV), a traditional anti-HIV drug, has anti-cancer effects. Some researchers have also shown NFV might be a potential P-gp inhibitor. This study is aimed at investigating whether nelfinavir can act as an MDR-reversal drug and to clarify its molecular mechanism as well. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Adriamycin could diffuse into the nucleus of HCC cells, interact with DNA and eventually induce apoptosis. There are some known mechanisms for development of adriamycin resistance of HCC [68][69][70][71][72][73][74][75]. Multiple miRNAs have been reported to be involved in adriamycin resistance in HCC ( Table 2).…”
Section: Mirnas and Resistance To Adriamycinmentioning
confidence: 99%
“…Adriamycin could diffuse into the nucleus of HCC cells, interact with DNA and eventually induce apoptosis. There are some known mechanisms for development of adriamycin resistance of HCC [68][69][70][71][72][73][74][75]. Multiple miRNAs have been reported to be involved in adriamycin resistance in HCC ( Table 2).…”
Section: Mirnas and Resistance To Adriamycinmentioning
confidence: 99%
“…Liu and colleagues corroborated nelfinavir-mediated depolarization of the mitochondrial membrane in doxorubicin-resistant CML cells, which resulted in a loss of adenosine triphosphate (ATP)-suggesting induction of metabolic stress. The authors further observed an increase in ROS level during the combination of suboptimal doses of doxorubicin and nelfinavir in doxorubicin-resistant CML cells [45]. Xiang et al showed enhanced intracellular and mitochondrial ROS production in cervical cancer cells; nelfinavir-mediated cellular apoptosis was rescued by the addition of antioxidant NAC and a mitochondria-targeting superoxide and alkyl-radical scavenger Mito-TEMPO, which indicates the role of oxidative stress in nelfinavir-induced cytotoxicity [33].…”
Section: Oxidative Stress and Mitochondriamentioning
confidence: 92%
“…However, decreased phosphorylation of ERK in cancer cells is not a universal response to nelfinavir treatment, as nelfinavir did not downregulate ERK phosphorylation in NSCLC [47], pancreatic cancer [101], and pituitary adenoma [105]. Downregulation of phospho-ERK in response to nelfinavir was further observed during combination with doxorubicin in doxorubicin-resistant chronic myeloid leukemia cells [45], and with bortezomib against MM cells [73]. Nelfinavir sensitized BRAF-mutated melanoma cells to MEK inhibitors and BRAF inhibitors via SMAD-mediated downregulation of PAX and MITF, and decreased phosphorylation of ERK during combination with inhibitors of MEK or BRAF [113].…”
Section: Signal Transduction Pathwaysmentioning
confidence: 97%
See 1 more Smart Citation
“…P-gp transported one molecule of the substrate across the membrane, requiring two molecules of ATP to provide energy (Robey et al, 2018). If the energy supply was insufficient, the efflux function of P-gp would be inhibited (Liu et al, 2018). Therefore, the content of intracellular ATP was measured to evaluate the effect of AE on P-gp function.…”
Section: Ae Reduced the Content Of Atp In Mcf-7/ Adr Cellsmentioning
confidence: 99%